AN OVARY STIMULATING FACTOR IN THE FRESHWATER PRAWN, MACROBRACHIUM LAMERRII - JAYALAKSHMI, K.; SAROJINI, R.; RAO, S. SAMBASIVA; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
In the present investigation effects of extracts of the central nervous system (brain and thoracic ganglion) and muscle tissue on ovarian development in the fieshwater prawn, M lamerrii have been studied. Both the brain and thoracic ganglion extracts stimulated vitellogenesis in oocytes. In particular, the brain extracts especially were more effective than those of thoracic ganglion in inducing ihis response. The extracts of muscle did not have any effect on the ovaries. These observations indicate that an ovary - stimulating factor in the central nervous system may act directly in ovarian vitellogenesis.